The effect of perceived risk in predicting gift purchase intention / Liew Cheng Siang - Liew , Cheng Siang (2018)
Purchasing a gift could be an extremely stressful task. In the purchase trajectory, the gift-giver not only needs to carefully select the gift but also has to ensure that the gift would evoke positive emotions. This stress could increase considerably if the recipient is a loved one. While there are several reasons for engaging in the gift-giving ‘ritual’, one fundamental reason is its potential to strengthen relationship ties between the giver and receiver. Research on gift-giving has long been conducted in disciplines such as anthropology, psychology and economics; marketing has also weighed into the research more recently due to the huge amount of money spent on gifts by givers each year. However, the marketing literature that specifically examines how consumers make gift purchases are lacking. Also, studies examining the specificities of the gifts as well as the role of the giver in the purchase process are scarce. This research investigates the influence of product factors (brand name and perceived quality) and personal factors (consumer knowledge and consumer involvement) on perceived risk. Next, this study investigates the influence of the indicated product factors, personal factors and perceived risk on purchase intention. Lastly, the study examines the mediating effect of risk that links the specified product and personal factors to purchase intention. For the methodology of the study, all the constructs used in the study were adopted from previous studies. A quota sampling based on gender and ethnicity was employed in order to reflect Malaysia’s population. Also, the survey for the current study was subjected to a pre-test procedure to ensure that the survey was appropriate for the study. A total of 447 responses were collected using self-administered questionnaires from general adults living in the Klang Valley area in Malaysia, which were used for further analysis. Structural Equation Modelling (SEM) was employed to analyse all the data collected. A two-step approach was adopted to examine the model of this research. The result from the measurement model was found to have a good fit. In addition, the results from the convergent validity, composite reliability and discriminant validity were valid and reliable. All the hypotheses proposed in this study were examined. Firstly, the study examined the product factors and personal factors influencing perceived risk. It was found that brand name, perceived quality and consumer involvement influence perceived risk. Interestingly, however, consumer knowledge was found to have an insignificant influence on perceived risk. Secondly, the study also examined the influence of product factors, personal factors and perceived risk on purchase intention. The results showed that all the hypotheses have a significant influence on purchase intention. Lastly, the study measured the mediating effect of perceived risk using the SEM bootstrapping method. Consumer knowledge was found to be insignificant in the study and was, therefore, not included in the analysis. The bootstrapping analysis indicated that perceived risk has a partially mediating effect between brand name and purchase intention and consumer involvement and purchase intention. On the other hand, the relationship between perceived quality and purchase intention showed that perceived risk has a full mediation effect. This study not only provides a great theoretical and methodological framework, but also a makes practical contribution. Retailers are able to craft a better marketing strategy and promotions to attract consumers to purchase products in their store. Overall, this study provides a better understanding of how a giver purchases a gift.